Let's Play - Murray, William; Illustrated by Russell, Chris (London Ladybird Books)
A reading scheme that uses the 'look and say' approach to learning to read. It introduces essential key words and regularly repeats it to assist with pronunciation and meaning.
Include Color Illustrations
Stories by Jill Corby
Keywords: Play -- Reading (Primary)